Comparison of Retinal Nerve Fiber Layer Thickness in Elderly Diabetic Patients with and without Peripheral Neuropathy - Bonifacio Buño II, MD; Darby Santiago, MD (Philippine Journal of Ophthalmology)
Objectives: The primary goal of this study was to determine the relationship between diabetic peripheral neuropathy and retinal nerve fiber layer (RNFL) thickness among elderly Filipinos with type 2 diabetes mellitus.